Analysis of Vannamei shrimp DNA fragment resistant to White Spot Virus Syndrome - Wiwien Mukti Andriyani; Sumini Sumini; Zeny Widiastuti (IJOTA (Indonesian Journal of Tropical Aquatic), 2021)
The attack of WSSV in Vannamei shrimp cultivation is still common. Shrimp quality improvement can be made through selection with the help of markers (marker-assisted choice). This study aimed to evaluate the DNA fragment profile of white shrimp that was resistant to WSSV disease. The analysis was performed using the PCR-RAPD method. WSSV challenged four groups of 100 Vannamei shrimp, then DNA was extracted from live and dead shrimp. The results showed that 2 of the 17 primers tested had high potential as markers, namely OP-09 and OPD-2. PCR products with OPC-09 primers had specific DNA bands measuring about 1.2 kb in all post-challenge WSSV resistant shrimp individuals. The amplification results using OPD-02 primers showed a particular band of DNA with a length of about 1.0 kb, with 60 % of the appearance in WSSV-resistant shrimp. In contrast, the WSSV-susceptible shrimp group did not have specific DNA fragments. Thus, the two RAPD primers had a high chance of being used in the selection with the help of markers to produce WSSV resistant shrimp.